Implementation of the Independent Learning Independent Campus (MBKM) Policy of the Teaching Assistance Program in Palu City - Zubair (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aims to: 1) analyze compliance in the implementation of MBKM policies for teaching assistance programs; 2) describe the smooth implementation of the MBKM policy for the teaching assistance program; and 3) describe the performance of the implementation of the MBKM policy of the teaching assistance program. The grand theory using Franklin & Ripley's policy implementation theory consists of; compliance, smoothness, and performance. The research was carried out at the State High School of Palu City with a qualitative method for 4 months with data collection techniques; interviews, documentation, and observations. Data analysis techniques using Miles and Huberman include; data collection, condentation, data display and conclusions. Viewed from the point of view of school needs, the results of the study show: 1) elements of Palu City State High School such as; school principals, vice principals for curriculum affairs and teachers have compliance in the implementation of the teaching assistance program; 2) the implementation of the teaching assistance program runs smoothly without significant obstacles seen in the smooth learning, completeness of learning administration, and the involvement of students of the teaching assistance program in various school programs; and 3) the implementation of the teaching assistance program on performance indicators, still needs development, especially in aspects; Innovation of learning models, application of learning technology, strengthening scientific content, and strengthening in the development of literacy and numeracy-based instruments.